Tackling the tensions in evaluating capacity strengthening for health research in low- and middle-income countries - Bates, Imelda (Health Policy Plan, 2015)
Strengthening research capacity in low- and middle-income countries is one of the most effective ways of advancing their health and development but the complexity and heterogeneity of health research capacity strengthening (RCS) initiatives means it is difficult to evaluate their effectiveness. Our study aimed to enhance understanding about these difficulties and to make recommendations about how to make health RCS evaluations more effective. Through discussions and surveys of health RCS funders, including the ESSENCE on Health Research initiative, we identified themes that were important to health RCS funders and used these to guide a systematic analysis of their evaluation reports. Eighteen reports, produced between 2000 and 2013, representing 12 evaluations, were purposefully selected from 54 reports provided by the funders to provide maximum variety. Text from the reports was extracted independently by two authors against a pre-designed framework. Information about the health RCS approaches, tensions and suggested solutions was re-constructed into a narrative. Throughout the process contacts in the health RCS funder agencies were involved in helping us to validate and interpret our results. The focus of the health RCS evaluations ranged from individuals and institutions to national, regional and global levels. Our analysis identified tensions around how much stakeholders should participate in an evaluation, the appropriate balance between measuring and learning and between a focus on short-term processes vs longer-term impact and sustainability. Suggested solutions to these tensions included early and ongoing stakeholder engagement in planning and evaluating health RCS, modelling of impact pathways and rapid assimilation of lessons learned for continuous improvement of decision making and programming. The use of developmental approaches could improve health RCS evaluations by addressing common tensions and promoting sustainability. Sharing learning about how to do robust and useful health RCS evaluations should happen alongside, not after, health RCS efforts.